РАДІОНУКЛІДНИЙ МОНІТОРИНГ ПРИ КАРЦИНОМІ НИРКИ - Ткаченко, М.М.; Романенко, Г.О.; Миронова, О.В.; Макаренко, А.В.; Гороть, І.В. (Українські медичні вісті, 2023)
РАДІОНУКЛІДНИЙ МОНІТОРИНГ ПРИ КАРЦИНОМІ НИРКИ